Market Orientation and Innovation Capabilities : Does it Impact the Performance of Small Businesses? - Hilal, M. I. M. (Indian Journal of Marketing, 2019)
The major objective of the study was to examine the impact of market orientation and innovation capability on the performance of small businesses in the Eastern Province of Sri Lanka. It was observed that many small businesses have emerged and are in existence after the prolonged war in the Eastern part of Sri Lanka and their sustainability should be secured. Therefore, it was essential to conduct a study on the market orientation and innovation capabilities of these small businesses. A sample of 234 executives, managers, or proprietors of small businesses which comprised of confectionaries, small restaurants, small textiles, and ice cream makers for selling were taken for the study. Analysis revealed that market orientation was lacking in the small businesses. In the case of market orientation, analysis revealed that business firms were not responding to the competitive actions. They were also lacking in competitive advantage based on customer needs. Analysis explained that the proprietors or managers did not discuss the competitors' strengths and weaknesses to formulate competitive strategies. Small businesses were also found to be in need of marketing skills, especially marketing planning and adopting market orientation. This implies that customers' behavior of products marketed by small businesses in the region should be well understood. The study recommended that the small businesses need to conduct training in marketing for proprietors, managers, and executives of small businesses in the region.